Approximate analytical dynamical mean-ﬁeld approach to strongly correlated electron systems - Stasyuk, I.V. (Condensed Matter Physics, 2000)
An approximate analytical scheme of the dynamical mean-ﬁeld theory
(DMFT), that is used for electron systems with Hubbard correlations and is
exact in the limit of the inﬁnite dimensionality of a space, is developed. The
effective single-site problem arising in the framework of this method is formulated in terms of the auxiliary Fermi-ﬁeld. The irreducible Green's function technique with the projecting on the Hubbard basis of Fermi-operators
is used for its solution. A system of DMFT equations is obtained in the
approximation which is a generalization of the Hubbard-III approximation
and combines it with a self-consistent renormalization of the local electron
levels. It is shown that the proposed approach includes as simple speciﬁc cases a number of known approximations (Hubbard-III, AA, MAA, . . . )
based on the assumption of the single-site structure of the electron self-
energy. У роботі розроблена наближена аналітична схема методу динамічного середнього поля (МДСП), який використовується для електронних систем з хаббардівськими кореляціями і є точним при безмежній
розмірності простору. Ефективна одновузлова задача, що виникає
в цьому методі, сформульована за допомогою допоміжного ферміполя. Для її розв’язання використано техніку незвідних функцій Гріна при проектуванні на хаббардівський базис фермі-операторів. Отримано систему рівняннь МДСП у наближенні, яке є узагальненням
наближення Хаббарда-ІІІ і поєднує його із самоузгодженим перенормуванням локальних електронних рівнів. Показано, що ряд відомих
наближень, що базуються на одновузловій структурі власноенергетичної частини електронної функції Гріна, є простими частинними випадками запропонованої схеми.